Multipolar hierarchy of efficient quantum polarization measures - De La Hoz, Pablo; Klimov, A. B.; Bjork, G.; Kim, Y. -H.; Mueller, C.; Marquardt, Christoph; Leuchs, Gerd; Sanchez-Soto, L. L.; Marquardt, Christoph (Physical Review A - Atomic, Molecular, and Optical Physics, 2013)
We advocate a simple multipole expansion of the polarization density matrix. The resulting multipoles appear as successive moments of the Stokes variables and can be obtained from feasible measurements. In terms of these multipoles we construct a whole hierarchy of measures that accurately assess higher-order polarization fluctuations. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05